1993
DOI: 10.1136/bmj.306.6882.895
|View full text |Cite
|
Sign up to set email alerts
|

Severity of inflammation of tympanic membrane as predictor of clinical course of recurrent acute otitis media.

Abstract: with standard management, reporting that they seemed to be a routine case for junior medical staff and had to wait until the end of regular operating lists for treatment.4 Medical management of miscarriage has the potential for resolving some of these issues and may have economic implications by freeing surgical resources for other uses.5 Randomised studies comparing medical with surgical management are required to evaluate this new method of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Assigning predictive value to colour of nasal discharge or sputum when suspecting sinusitis has been described [16]. Examination of the eardrum is a key component in GPs' diagnosis of acute otitis media [17], although its appearance might not predict the clinical course [18]. Physicians' concerns regarding rapid streptococcus tests are known from the literature [19].…”
Section: Discussionmentioning
confidence: 99%
“…Assigning predictive value to colour of nasal discharge or sputum when suspecting sinusitis has been described [16]. Examination of the eardrum is a key component in GPs' diagnosis of acute otitis media [17], although its appearance might not predict the clinical course [18]. Physicians' concerns regarding rapid streptococcus tests are known from the literature [19].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we defined a GP-diagnosis of AOM as an ICPC code H71 recorded in the GP health records. Variation in AOM coding between GPs and misclassification of AOM cannot be ruled out, in particular in this young age group where otoscopic confirmation is known to be difficult [ 23 ]. Furthermore, a GP-diagnostic code was not available for 39 of the 326 (12%) GP-consultations.…”
Section: Discussionmentioning
confidence: 99%
“…Appelman et al found that signs of tympanic inflammation did not predict the course of acute otitis media. 1 Pneumatic otoscopy was proposed as an alternative criteria, but a review by Preston showed that pneumatic otoscopy predicted only serous otitis and not acute otitis media. 2 Therefore, accurate diagnosis is still an issue and confounds conclusions about outcomes.…”
Section: Commentarymentioning
confidence: 99%